1989
DOI: 10.1148/radiographics.9.4.2756192
|View full text |Cite
|
Sign up to set email alerts
|

The clavicle: normal and abnormal.

Abstract: The clavicle is an unusual long bone with many unique embiyologic features. It is often involved in congenital and acquired disorders. Traumatic, inflammato,y, neoplastic, metabollc and many other miscellaneous lesions may also affect the bone. Because of its Ilgamentous attachments and the presence ofarticulations at both ends, the clavicle can also be involved in arthrffic diseases. This article Illustrates the radiographic manifestations ofmany ofthe disorders of the clavicle that are commonly encountered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…This foramen transmits the nutrient artery and at times, the supraclavicular nerve. 19 In contrast, Knudsen et al reported that clavicle is supplied by periosteal arteries and the nutrient artery is not found. 18 however few authors suggested that suprascapular artery supplies the middle third region of the clavicle by a nutrient branch.…”
Section: Introductionmentioning
confidence: 94%
“…This foramen transmits the nutrient artery and at times, the supraclavicular nerve. 19 In contrast, Knudsen et al reported that clavicle is supplied by periosteal arteries and the nutrient artery is not found. 18 however few authors suggested that suprascapular artery supplies the middle third region of the clavicle by a nutrient branch.…”
Section: Introductionmentioning
confidence: 94%
“…The clavicle is the first bone that starts process of bone ossification but it is the last bone that completely fuses (Gardner 1968;Kumar et al 1989;Ogata & Uhthoff 1990). The clavicle has not medullary cavity like other long bones and it is the first foetal bone to get ossification by only membranous ossification like other long bones (Kumar et al 1989;Ogden et al 1979;Scheuer & Blach 2004). The clavicle of human has been reported to complete fusing this bone that approximate 25 years old (Ogata & Uhthoff 1990).…”
Section: The Process Of Clavicle Ossificationmentioning
confidence: 99%
“…The ossification initially starts with two primary ossification centers from medial end and lateral end that fuse together in shaft of clavicle during 5 th and 6 th foetal week (Kumar et al 1989;Moore et al 2011;Ogden et al 1979;Scheuer & Blach 2004). In 5 th week, ossification center of clavicle presents primary center of ossification; medial and lateral centers; at shaft of clavicle and fuse in 6 th week of development of embryo (Kumar et al 1989;Ogden et al 1979;Scheuer & Blach 2004). Then, secondary ossification begins develop at sternal end and acromial end from mesenchymal tissue.…”
Section: The Process Of Clavicle Ossificationmentioning
confidence: 99%
“…A large rhomboid fossa could be mistaken for a lytic lesion. 20 The coracoclavicular ligament, composed of the trapezoid and the conoid ligaments, extends from the inferior surface of the clavicle to the coracoid process of the scapula. A bony prominence, known as the conoid tubercle or coracoid tuberosity, may be seen at the attachment site of the coracoclavicular ligament along the inferior aspect of the distal clavicle (Fig.…”
Section: Appearance Of Tendinous and Ligamentous Insertions Claviclementioning
confidence: 99%